(3GdLhGH Gdbhje Yf GdSDGd GdeJYdb HEbWGY GdSjO Jejes - (3CHh GdehGgH fLe GdOjf eMeO Hf CMeO Hf CHj HcQ GdZjWj GdScfOQj GdTGaYj,J (B981 (3g` s ((3GdbOS GdTQja s)
(3ChdgG (B:s
(3HYO agPG LhGH bhje Yf SDGd hQO Ydi jJYdb HEbWGY GdSjO Jeje heG hQO ai Pdc ef GdMOjK Yf GdfHi GdcQje s
(3BNQgG (B:s
(3EPG de jVQ GdbdY HGdCQV aEf CVQHgG aYd eG gh dGMX ef Jedc hGddg SHMGfg hJYGdi CYde HGdUhGH hEdjg GdeQLY hGdeBH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3GdebUhO Hg Jeje GdOGQis
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdCSJGP GdOcJhQ ESMGb ehSi GdMSfi GdNGUI s
Keywords: (3Gdabg GdTGaYjs